Perlindungan Hukum Terhadap Keselamatan Kerja Bagi Tenaga Kesehatan Akibat Pandemi Covid-19 - Theresia Louize Pesulima; Yosia Hetharie (Faculty of Law, Universitas Pattimura, 2020)
Indonesia is entering a critical period of the Covid-19 pandemic. Health workers are a profession that is in the vanguard and fight directly against Covid-19. Under these conditions, sometimes health workers have to sacrifice their lives to protect the public from the spread of the Covid-19 pandemic. From the results of the discussion, it can be concluded that the legal protection of the workforce safety of health workers due to the Covid-19 pandemic has not been implemented properly as mandated in the legislation. In the implementation of the rights of health workers during the Covid-19 pandemic still neglected and have not been fulfilled. Therefore, the role and responsibilities of the global government are needed to fulfill the rights of health workers as the frontline in handling the spread of Covid-19 in Indonesia.